Eksplorasi etnomatematika dalam pembelajaran matematika berbasis kearifan lokal untuk meningkatkan literasi numerasi siswa - Zakiya, Affifatus (Maliki Interdisciplinary Journal, 2026)
Numeracy literacy is a fundamental skill that shapes students readiness to meet the challenges of the twenty first century. However, results from international assessments such as PISA and national evaluations like AKM indicate that Indonesian students numeracy literacy still requires significant improvement. Ethnomathematics, which explores the connection between mathematical concepts and local cultural contexts, provides a learning approach that is contextual, meaningful, and closely related to students daily experiences. This article presents a theoretical study on how the exploration of ethnomathematics based on local wisdom can be integrated into mathematics learning to strengthen students numeracy literacy. The method applied is a literature review with a descriptive analytical approach. The findings reveal that Indonesian cultural artifacts such as batik, weaving, traditional architecture, and traditional games contain rich mathematical ideas including geometric transformations, patterns and sequences, number systems, and probability. Incorporating these concepts into classroom practice through ethnomathematical perspectives has been shown to enhance student motivation and deepen conceptual understanding. The study recommends the development of mathematics learning modules that draw upon local ethnomathematics as a strategic effort to contextualize the national mathematics curriculum, making it more relevant to students cultural backgrounds and lived experiences.